Conservation Genetics and Breeding using Molecular Genetic Markers in Japanese Quail (Coturnix japonica) - Michael N. Romanov; Questan Ali Ameen; Ahmed Sami Shaker; Rana Mohammed Al-Obaidi; Darren K. Griffin (Frontiers in Bioscience-Scholar)
Background: The Japanese quail (Coturnix japonica) is a small migratory bird whose main habitats are located in East Asia, Russia, China, Japan, Korea, and India. The Japanese quail was first introduced into the Iraqi research sector in the early 1980s. This investigation aimed to identify the genetic divergence between the available genetic lines of the Japanese quail in Iraq as a first step to conducting further conservation and breeding, benefiting from studying the genetic diversity related to productivity, adaptation, and immune susceptibility. Methods: In this study, we harnessed the random amplified polymorphic DNA (RAPD)-polymerase chain reaction (PCR) protocol to investigate the genetic structure, diversity, and differentiation of seven distinct genetic lines of these birds with white, brown, wild grey, and yellow plumage guided by 20 molecular genetic markers. Results: Our findings showed a relatively high polymorphism level of these 20 markers, which was adequate for describing genetic variation within and between the quail lines under study. Overall, the pairs of the White male and Brown male, Brown female and Grey male, and Grey female and Grey male lines were the most genetically distant. Conversely, the White male and Grey male lines were the most similar. Conclusions: The genetic differences established between these lines can enable us to suggest recommendations for further conservation genetics and breeding of this species. In particular, we propose that choosing animals (lines) with the greatest genetic distances, i.e., the least genetic similarities, can help preserve the highest genetic variability within the population. This proposed approach mirrors many contemporary conservation strategies, and information derived directly from this study can potentially be used to improve breeder selection regimes for additional conservation initiatives ex situ.